AN IMPROVED IMAGE-BASED PROPAGATION MODEL FOR INDOOR AND OUTDOOR COMMUNICATION CHANNELS - Teh, C. H.; Chuah, H. T. (2003)
In this paper, an improved image-based propagation model based on a novel polygon-tracing technique is presented. Unlike other image-based models, it uses generic plane polygons, which we term as ray-polygons, to keep track of rays. Binary Space Partitioning is employed to provide the object visibility order necessary for polygon tracing. The proposed model has a variety of advantages, namely efficient, without reception sphere and ray separation issues, and having less geometrical restrictions. It can be applied equally well in indoor and outdoor environments.